Mutual Relationship Management Between Teachers and Parents: Strategies for Improving Student Learning Outcomes - Tantowi, Ahmad; Subhan, Ali; Romadon, Sahri; Rosidin, Rosidin (JURNAL AL-TANZIM, 2022)
This study aims to understand the mutual relationship between teachers and parents in improving student learning outcomes. The site of this research is SMA NU 01 Al-Hidayah Kendal. This research uses a qualitative case study approach, where the researcher tries to understand the meaning behind the phenomena that occur in the field through interviews, observations, and documentation. The results showed that the mutual relationship built by the school to make teachers and parents more intimate in improving student learning outcomes was carried out through careful and systematic planning by involving all school parties to obtain optimal results. The planning carried out then carried out optimally and carried out jointly by the school with a mutualistic symbiotic principle and continued with an evaluation with the principle of continuous improvement.